Efficiency of the bicycle operation under various tactical variants - Kolumbet, A. N.; Bazulyuk, T. A.; Dudorova, L. Y.; Chernovsky, S. M.; Maximovich , N. Y. (Physical Education of Students, 2017)
Aim: to determine the efficiency of the cyclist in various tactical options. Material: In the experiments participated athletes (n = 6) of high qualification (mean age - 19.8 ± 1.3 years, mean weight - 71.4 ± 3.5 kg). As a model of the individual pursuit race at 4 km, a five-minute pedaling on the bicycle ergometer was used. Series of loads was set on the modernized mechanical bicycle ergometer "Monark" . The five-minute bicycle ergometer test is similar to the individual pursuit race at 4 km: according to the time of the exercise; on the frequency of pedaling (110-120 rpm); on the frequency of heartbeats. Results: Tactical variants in the pursuit race at 4 km are considered. The total work in a free test was on average 106.38 ± 3.57 kJ. The operating energy consumption is on average for 379.0±16.1 kJ. The operating efficiency (economy) of the exercise attained on average for 28.0 ± 0.75%. This corresponds to the effectiveness of aerobic work of moderate power. The ratio of aerobic and anaerobic contributions to the provision of work was 77.3 and 22.7%. The smallest work was done in a test with step-increasing power. The athletes performed the closest work to the given job in the test with a variable (±15%) operating mode. The shortfall in it was on average for 0.46%. The absence of reliable differences in the economics of the work did not allow us to identify a rational variant of power distribution for an exercise lasting 5 minutes. Conclusions: Tactical options in the pursuit race for 4 km depend on the features of the power systems of the rider. When optimizing tactics, it is necessary to select an individually optimal variant of the distribution of forces at a distance.